10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Global health diplomacy is central to shaping the international response to health challenges, yet what counts as "success" or "failure" remains contested. This study explores how gender and geopolitical identity influence perceptions of success and failure among global health diplomacy practitioners. Drawing on qualitative analysis of free-text responses from 136 professionals worldwide, we identify distinct narrative patterns. Women and Global South respondents emphasized normative goals: equity, justice, and structural reform, framing success in terms of inclusion, voice, and redistribution. In contrast, men and Global North respondents often framed success through processes: institutional innovation, efficiency, and procedural legitimacy. Failures were similarly divergent, seen as systemic exclusion and dependency by some, and as governance breakdowns or missed diplomatic opportunities by others. Our findings highlight the plurality of diplomatic worldviews and call for a more reflexive, inclusive approach to evaluating and practicing global health diplomacy that recognizes diverse epistemologies and power dynamics shaping the field.